Redesign UI/UX Website Promedika Menggunakan Metode Design Thinking pada PT Promedika Mitra Utama Samarinda - Salsabila, Haira; Natasia, Sri Rahayu; Putera, M. Ihsan Alfani; Soffa, Is Rio Sena Nur (Equiva Journal, 2024)
One of the organizations that uses the website is PT Promedika Mitra Utama Samarinda. Since its establishment in 2011, the company has been serving wholesale and retail purchases with various medical device needs for hospitals, individuals, laboratory equipment, HSE safety equipment, and dentistry. The problems contained on the website are that the website is still less informative and less interactive to users, user needs for detailed and credible information related to medical devices, user needs for effective and efficient sales features, and too many components on the website. Therefore, it is necessary to redesign the UI / UX of the website to be able to meet the needs of the company and the needs of users. The stages of research carried out using design thinking methods, namely empathize, define, ideate, prototype, and test. This research produces recommendations for design solutions based on problem analysis and idea solutions that have been made in terms of convenience aspects. The results of the research obtained, namely the category of current website problems in terms of customer service, copywriting, and system flow. This study produced the results of 9 menu design solutions that have a good level of ease of use based on the results of usability testing with the SEQ (Single Ease Question) method on 9 tasks carried out by 5 respondents with an average value from 6 to 6.8.